Complete genome sequencing and in silico genome mining reveal the promising metabolic potential in Streptomyces strain CS-7 - Alam, Khorshed; Hao, Jinfang; Zhong, Lin; Fan, Guoqing; Ouyang, Qing; Islam, Md. Mahmudul; Islam, Saiful; Sun, Hongluan; Zhang, Youming; Li, Ruijuan; Li, Aiying (Frontiers in Microbiology, 2022)
Gram-positive Streptomyces bacteria can produce valuable antibiotics and secondary metabolites. Streptomyces genomes include huge unknown silent natural product (NP) biosynthetic gene clusters (BGCs), making them a potential drug discovery repository. In order to collect antibiotic-producing bacteria from unexplored areas, we identified Streptomyces spp. CS-7 from mountain soil samples in Changsha, P.R. China, which showed strong antibacterial activity. Complete genome sequencing and prediction in silico revealed that its 8.4 Mbp genome contains a total of 36 BGCs for NPs. We purified two important antibiotics from this strain, which were structurally elucidated to be mayamycin and mayamycin B active against Staphylococcus aureus. The data here supported this Streptomyces species especially from unexplored habitats has a high potential for new NPs.